ECONOMIC FREEDOM - Altin, Hakan (European Scientific Journal, ESJ, 2014)
It is not easy to define economic freedom concept and the area it encompasses. In this research, the existence of positive economic growth promised by economic freedom is investigated. As the result of the implementation, the existence of economic growth was encountered. However, the existence of this positive impact is not the same for every country. Results of the implementation can be interpreted in both ways. First of them is that economic freedom ensures the economic benefit. The second one is the fact that ground should be gained in terms of making the profit promised by economic freedom and in terms of the meanings contained by economic freedom.